Estimation of Se(VI)/Se(IV) ratio in water by the ratio recorded in barite. (12th November 2013) - Tokunaga, Kohei; Yokoyama, Yuka; Takahashi, Yoshio
<x xml:space="preserve">Abstract</x> [1] It is possible that the distribution behaviors of redox‐sensitive elements such as selenium (Se) between authigenic minerals and water can provide information on the oxidation state of the element in the coexistent water during mineral deposition. Considering the similar chemical characteristics of Se(IV) and Se(VI) oxyanions, we propose that the Se(VI)/Se(IV) ratio in a particular precipitate, such as barite, may enable us to estimate the Se(VI)/Se(IV) ratio in the coexistent water. The coprecipitation experiments of Se with barite coupled with the determination of the oxidation state of Se both in the aqueous phase and in barite were conducted by Se K‐edge X‐ray absorption near‐edge structure and high‐performance liquid chromatography connected to inductively coupled plasma‐mass spectrometry, respectively, to investigate the influence of the oxidation state of Se on its immobilization into barite at pH 4.0 and 8.0. The results showed that the Se(VI)/Se(IV) ratio in barite was correlated with the Se(VI)/Se(IV) ratio in water, which in turn can provide physicochemical and biogeochemical information related to the Se(VI)/Se(IV) ratio in water in the environment where barite precipitated.